Pengaruh Disiplin Kerja dan Kerjasama terhadap Kinerja Karyawan pada Perusahaan PT Sarana Lalu Lintas Medan - Setiawan, Angga; Bahtiar, Bahtiar; Syafrizal, Syafrizal (Universitas Islam Islam Sumatera Utara, 2022)
The formulation of the problem in this research is how work discipline and cooperation influence employee performance at the company PT Sarana Lalu Lintas Medan. What is the influence of work discipline and cooperation at PT Sarana Lalu Lintas Medan. The population in this research is all employees of PT Sarana Lalu Lintas Medan, totaling 30 people and the entire population is used as a sample. This research approach is a quantitative approach. This testing method uses multiple linear regression analysis techniques. Based on the test results and analysis, it shows that there is a significant influence of work discipline variables on the performance of PT Sarana Lalu Lintas Medan employees. There is a significant influence of the collaboration variable on the employee performance variable of PT Sarana Lintas Medan. Work discipline and cooperation have a significant effect on the performance of PT Sarana Lintas Medan employees